QTL Mapping and Validation of Adult Plant Resistance to Stripe Rust in Chinese Wheat Landrace Humai 15 - Yuan, Feng-Ping; Zeng, Qing-Dong; Wu, Jian-Hui; Wang, Qi-Lin; Yang, Zu-Jun; Liang, Bang-Ping; Kang, Zhen-Sheng; Chen, Xin-Hong; Han, De-Jun (Frontiers in Plant Science, 2018)
Stripe rust caused by Puccinia striiformis f. sp. tritici (Pst) is a devastating foliar disease that affects common wheat and barley throughout the world. The reasonable deployment of adult plant resistance (APR) wheat varieties is one of the best methods for controlling this disease. Wheat landraces are valuable resources for identifying the genes/QTLs responsible for disease resistance. Humai 15 is a Chinese spring wheat landrace and it has exhibited adequate levels of APR to the prevalent Pst races in field environments for many years. In this study, a population of 177 recombinant inbred lines (RILs) was derived from Humai 15  Mingxian 169. After screening based on a 90K chip array using 45 RILs and Kompetitive Allelic Specific PCR marker genotyping for the population of RILs, a major effect QTL in Humai 15 was located on the centromere of chromosome 2B, where it accounted for up to 47.2% of the phenotypic variation. Two other minor QTL genes from Humai 15 were located on chromosome arms 3BS and 4BL. The Yr18 gene was identified on chromosome arm 7DS in Mingxian 169.